Marxian critique of equality in modern citizenship - del Aguila Marchena, Levy (Estudios de Filosofía, 2020)
This paper sets forth Marx’s critique of equality as an essential dimension of modern citizenship. For this purpose, the paper traces a link between the early Marxian critique to the citizen “celestial sphere” with the ways in which production and circulation processes are articulated to set up modern societies, according to the commercial logic and the logic of capital. According to our thesis, Marx’s political economy provides some elements to better understand, and in a more comprehensive way, his early criticism, particularly about the relationship between the public and the private, and about the place of the citizen equality in the capitalist society.